Advanced HCC Patient Benefit From Neoantigen Reactive T Cells Based Immunotherapy: A Case Report - Liu, Chenxi; Shao, Jie; Dong, Yanbing; Xu, Qiuping; Zou, Zhengyun; Chen, Fangjun; Yan, Jing; Liu, Juan; Li, Shuangshuang; Liu, Baorui; Shen, Jie (Frontiers in Immunology, 2021)
Advanced hepatocellular carcinoma（HCC）is a highly lethal disease, mainly due to the late stage at diagnosis and its rapid progression. Although patients with advanced HCC can choose targeted therapy or chemotherapy, overall, the treatment response rate is extremely low and the average survival time is one year more or less. But the application of immunotherapy have led to a paradigm shift in the treatment of HCC, such as TILs (tumor infiltrating lymphocytes),Checkpoint blockade (immune Checkpoint blockade), CAR-T(chimeric antigen receptor T cells) and TCR-T (engineered t-cell receptor T cells). And recent data indicate neoantigens generated when tumors mutate are the main target of tumor-specific TILs, and they are also the main antigens mediating tumor regression in TILs treatment.Moreover, numerous evidence have revealed that radiotherapy lead to massive release of tumor antigens, which may increase the effectiveness of immunotherapy.Based on the above theory, we used neoantigen reactive T cells combined with tomotherapy to treat a patient with advanced HCC (Clinical Trial Study Registration Number: NCT03199807), who reached a long time progress free survival.